WHAT, WHY AND HOW OF TRANSLATIONAL RESEARCH IN VETERINARY SCIENCES – A SMALL BEGINNING AT TANUVAS - G. Dhinakar Raj; S. R. Rao; S. Thilagar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
In 2100, the global population is expected to cross 10.1 billion, almost 50% more than the present 7 billion. India would replace China as the most populous country in the world. This increasing population puts tremendous pressure on our agricultural systems to produce more food, feed and fibre on limited and decreasing land area, reducing water resources and deprived soils. In this context, the role of animal sector assumes greater significance to support and complement the agricultural productivity to feed the growing millions.